Differences in fungicide resistance profiles and multiple resistance to a quinone‐outside inhibitor (QoI), two succinate dehydrogenase inhibitors (SDHI), and a demethylation inhibitor (DMI) for two Stagonosporopsis species causing gummy stem blight of cucurbits. Issue 11 (17th April 2019) - Li, Hao‐Xi; Nuckols, Thomas A; Harris, Devon; Stevenson, Katherine L; Brewer, Marin T
ABSTRACT: Background: Gummy stem blight (GSB) is a devastating disease of cucurbits that has been effectively managed with fungicide applications. However, the Stagonosporopsis spp. that cause GSB have rapidly evolved resistance to multiple classes of fungicides. To better understand the evolution and persistence of fungicide resistance in field populations, resistance profiles of unique and clonal genotypes of 113 Stagonosporopsis citrulli and 19 S. caricae isolates to four different fungicides were determined based on in vitro mycelial growth assays and molecular markers based on genes encoding fungicide targets. Results: All 19 S. caricae isolates screened were resistant to tebuconazole and azoxystrobin, and sensitive to boscalid and fluopyram. All 113 S. citrulli isolates were sensitive to tebuconazole and sensitive to fluopyram, with one exception that was fluopyram‐resistant. All isolates of S. citrulli except two were resistant to azoxystrobin. Phenotypic differences in response to boscalid were detected among S. citrulli isolates, but the phenotypes were not associated with multilocus genotypes (MLG) determined by 16 microsatellite loci. Additionally, isolates sharing the same MLG varied by SdhB genotype. A unique mutation of I229V in SdhB, a target of succinate dehydrogenase inhibitor fungicides, was detected for the fluopyram‐resistant isolate of S. citrulli . Conclusion: Both the lack of association of fungicide resistance profiles with genetic similarity of isolates based on microsatellite loci and the finding that widely distributed MLG varied in fungicide resistance profiles suggest that independent evolutionary events for resistance to boscalid have likely occurred. Frequent genetic recombination within populations may be responsible for resistance to multiple fungicides. This study provides useful information for effectively managing both species of GSB fungi present in the southeastern USA and understanding the evolution of fungicide resistance within populations of plant‐pathogenic fungi. © 2019 Society of Chemical Industry Abstract : We detected six fungicide resistance profiles to four fungicides in the gummy stem blight of cucurbit pathogens Stagonosporopsis citrulli and S. caricae .